2015
DOI: 10.1159/000430285
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Macrophages Promotes Development of Diabetic Encephalopathy

Abstract: Background/Aims: Diabetes and Alzheimer's disease are often associated with each other, whereas the relationship between two diseases is ill-defined. Although hyperglycemia during diabetes is a major cause of encephalopathy, diabetes may also cause chronic inflammatory complications including peripheral neuropathy. Hence the role and the characteristics of inflammatory macrophages in the development of diabetic encephalopathy need to be clarified. Methods: Diabetes were induced in mice by i.p. injection of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The M1 macrophages express nitric oxide synthase (iNOS) and some pro-inflammatory cytokines and toxin like reactive oxygen species (ROS) [34][35][36][37]. M2 macrophages are specified as expression of arginase, and surface markers CD163, CD206 and CD301 that are not expressed by M1 macrophages [11,23,24,26,[34][35][36][37][38][39][40]. Macrophage polarization has been shown to regulate a variety of biological processes, as recently nicely reviewed [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The M1 macrophages express nitric oxide synthase (iNOS) and some pro-inflammatory cytokines and toxin like reactive oxygen species (ROS) [34][35][36][37]. M2 macrophages are specified as expression of arginase, and surface markers CD163, CD206 and CD301 that are not expressed by M1 macrophages [11,23,24,26,[34][35][36][37][38][39][40]. Macrophage polarization has been shown to regulate a variety of biological processes, as recently nicely reviewed [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic hyperglycemia is the main trigger for the development of DE, past studies have shown that inflammatory damage to the brain also predisposes to disease progression [ 8 ]. Recently, in a mouse STZ-induced diabetes model, we have shown the centrality of recruited and infiltrated inflammatory macrophages in the mouse brain, to the progression of DE [ 9 ]. In the current study, our first aim was to investigate if this recruitment and infiltration of inflammatory macrophages in the brain are similarly required for DE development in diabetic rats, an animal model that more closely resembles human diabetes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that diabetic encephalopathy (DE) is caused primarily by constitutive hyperglycemia [ 2 ], although recent evidence suggests that oxidative stress and brain inflammation promote the development of DE and associated neurodegenerative diseases [ 3 7 ], highlighting a specific role for activated infiltrating macrophages in disease progression [ 8 ]. Recently, we reported that DE could be suppressed through depletion of inflammatory macrophages, without affecting the underlying diabetic status [ 9 ]. However, the molecular regulation of inflammatory macrophages in diabetes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…With study progressing, this nature has been recognized to play an important role in the development of DCI. There is a study demonstrated that macrophage activation and infiltration in the nervous system can lead to chronic degenerative disease of the central nervous system (Kierdorf et al, 2010), and blockade the activation of macrophage can significantly decrease levels of malondialdehyde, catalase and superoxide-positive cells in the brain (Wang et al, 2015). …”
Section: The Pathogenesis Of Diabetic Encephalopathymentioning
confidence: 99%